STRATEGI MANAJEMEN PEMBIAYAAN DALAM MENGELOLA DANA BEASISWA DI SMAN 1 AWAYAN - Miranti Miranti (CV. ADIBA ASIHA AMIRA, 2025)
Effective management of scholarship funds is essential to ensure that educational assistance is on target and sustainable. SMAN 1 Awayan implements a financing management strategy to improve transparency and efficiency in managing scholarship funds. This study aims to analyze the financing management strategy in managing scholarship funds at the school, focusing on planning, recipient selection, distribution, and program evaluation. This study uses a qualitative method with a case study approach. Data were collected through interviews with the school, analysis of financial documents, and observation of the implementation of the scholarship program. Data analysis techniques involve data reduction, data presentation, and drawing conclusions. The results of the study indicate that SMAN 1 Awayan implements needs-based planning with systematic recording. Recipient selection is carried out transparently based on academic achievement and economic conditions. Fund distribution is carried out through bank transfers to avoid misuse. Periodic evaluations are carried out to ensure the effectiveness of the program. This strategy has been proven to be able to increase student learning motivation, improve academic achievement, and reduce dropout rates. In conclusion, a systematic and transparent financing management strategy contributes to the effectiveness of scholarship fund management. Recommendations for schools are to improve the monitoring and evaluation system to strengthen the sustainability of the scholarship program